ANALISIS RESEPSI KHALAYAK TERHADAP PEMBERITAAN MAKAN SIANG GRATIS DI MEDIA MASSA - Azizi, Adira Dzaki; Vera, Nawiroh (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2024)
The mass media coverage during the recent presidential campaign highlighted one of the programs proposed by the Prabowo-Gibran pair, namely the "free lunch" initiative. This news attracted significant public attention. This study aims to analyze the public's reception of the news about the free lunch program. This research is a qualitative study. Data were obtained through in-depth interviews with several informants representing various social backgrounds. Analysis was conducted based on Stuart Hall's encoding-decoding theory, which emphasizes that audiences do not merely receive information passively but also assign their own meanings to the messages they receive according to their social, cultural, and ideological contexts. The results of the study show three main categories of audience reception: dominant-hegemonic, negotiated, and oppositional. Audiences with a dominant-hegemonic reception tend to view the coverage as a positive policy beneficial to the broader society. Those with a negotiated reception recognize the benefits of the program but remain critical of certain aspects of its implementation, such as effectiveness and sustainability. Meanwhile, audiences with an oppositional reception tend to see the free lunch program as a policy that is not well-targeted and does not fully address health issues, appearing as mere political rhetoric.